An overview of the adaptation strategies in the tourism industry during pandemic covid 19 - Mazlan, Nur Adilah; Ahmad, Siti Yuliandi Ahmad (Mindware PLT, 2021)
The world was catastrophic when an illness virus known as novel coronavirus COVID-19 occurred in China in December 2019. The virus is widespread, and the pandemic impacted most industries in the first quarter of 2020. The tourism activities stopped to maintain safety and prevent the virus from spreading further. Thus the tourism industry hit the hardest. Travel agencies, hotels, and the aviation industry were among tourism-related businesses that had to close. This research aims to identify the adaptation strategies by the tourism industry for increasing and reactivating post-covid tourism activity. This study approached a systematic literature review with the secondary data from the ten previous studies. The main findings show that the tour operators are preparing a few new strategies to adapt to the pandemic and new norms in the tourism industry. As a result, the tourist sector was reopened in a few phases in line with government guidelines to slow the pandemic and revive the tourism economy. The research illustrates how the global tourism sector adjusts to the new normal and develop new strategies to resurrect the business. The recommendations are that Malaysian tourism operators can adapt and emulate some of the methods used by other countries to restore the tourist industry’s glory. For example, travel agencies can collaborate with hotels, airlines, and tourist destinations to do approximately new tourist packages a few days after the quarantine. This approach can assist small businesses to recover from the effects of the covid-19 epidemic while indirectly contributing to the economy. With the cooperation of various parties in the tourism industry and tourists, it is possible to help boost its economy. To some extent, while also allowing tourists to 115 return to travel with a new normal and adhere to the rules set by certain national governments to control the spread of covid-19